How can a seemingly weak state in the financial services industry act strong? The role of organizational policy capacity in monetary and macroprudential policy. (November 2019) - Bakır, Caner; Çoban, Mehmet Kerem
Abstract: It is widely held in the public policy and political economy literatures that the Turkish state is weak and cannot adopt a proactive approach in the financial services industry by steering and coordinating the financial policy network. However, it is puzzling that this seemingly "weak" Turkish state, which is often marked by fragmentation, conflict, and a lack of policy coordination within the state apparatus, acted strongly between 2010 and 2016 by taking pre-emptive measures to contain the macrofinancial risks arising from hot money inflows and bank credit expansion. Examining the organizational policy capacity of the Central Bank of the Republic of Turkey, this article argues that proactive policy design and implementation are more likely to complement state capacity when the principal bureaucratic actors have strong organizational policy capacities.